Analisis Strategi Pemasaran Dan Inovasi Produk Dalam Meningkatkan Volume Penjualan Usaha Kecil Menengah ( Studi Pada UMKM Ice Cream El Faris ) - Nurbaniah, Risa Siti; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze marketing strategies and product innovation in increasing the sales volume of the El Faris Ice Cream MSME. The research method used is descriptive qualitative, with date collected throught observation, interviews, and documentation. The finding show that El Faris applies marketing strategies through distribution to school kiosks and social event, while focusing on taste quality as the product’s main value. Innovation is implemented by improving raw materials to enhance the product’s taste and texture. Major challenges include limited capital, inconsistent availability of raw materials, and competition with large companies. Nevertheless, consistency in quality and customer service, along with direct consumer engagement, are key factors for El Faris’s success in expanding its market and maintaining customer loyality.